The effectiveness of sport within social intervention projects: a UK case study - Crisp, P. (Physical Culture and Sport. Studies and Research, 2021)
In the UK, successive governments have prioritised the use of sport for developmental purposes, a range of broader com-munity matters, and as a purposeful tool to help at-risk youth. However, given the accepted wisdom underpinning the continued investment in sports projects that reflect ideas centred on youth and community development, it is not unsur-prising that a number of authors (for instance, Coalter, 2007; Griffiths and Armour, 2011) question the validity and true nature of using sport in this context. This is especially so when some research indicates that it may well be the schemes, people, or ancillary benefits within projects that are the primary factor in any appreciable change in pro-social behaviours, rather than sport per se (Sandford, Armour, and Duncombe, 2008). This study used interviews with eight experienced community sport development officers, coaches, and project organisers in the south of the UK. The findings revealed that sport and social intervention projects could develop participants` self-esteem, resilience, and aspirations, and that sport was seen as a helpful tool to help facilitate this. However, the findings also emphasised that any meaningful changes in behaviour were also subject, and subordinate to, the importance of developing positive coach-participant relationships. The implications are discussed within the paper.